NATIONAL DIGITAL LIBRARY STRATEGIES: A SOUTH AFRICAN PERSPECTIVE - Drijfhout, Douwe; Ledwaba, Lesiba (My University, 2012)
The objects of the National Library of South Africa (NLSA) and the functions it is required to perform are prescribed by the National Libraries Act, Act 92 of 1998. The NLSA is the primary resource of South African published documentary heritage. The NLSA strives to ensure equitable access to its comprehensive collections for all members of South African society. The National Library’s collections contain a wealth of information including South African books, periodicals, newspapers, maps, special collections, government publications and foreign official publications.
Keywords: NATIONAL DIGITAL LIBRARY STRATEGIES: A SOUTH AFRICAN PERSPECTIVE